PENINGKATAN HASIL BELAJAR SISWA KELAS 3 PELAJARAN IPA MATERI PERUBAHAN WUJUD BENDA MELALUI MODEL PBL - Munazilah; Endang Suprapti; Umi Arsiyati (PROCEEDING UMSURABAYA, 2024)
This research was carried out based on findings which showed that the 4C skills (Communication, Collaboration, Creativity and Innovation, Critical Thinking and Problem Solving) of class III students at Merarai 9th Elementary School were still low. The aim of this research is to improve the students' 4C skills. The learning model that can improve students' 4C skills to have 4C skills is the Problem Based Learning (PBL) model. A learning approach that can be integrated with the PBL model is the STEAM (Science, Technology, Engineering, Art, Mathematics) approach. The method used in the research is a quantitative method, while the design used is Classroom Action Research (PTK). Based on the results of this research, the author applies the STEAM integrated PBL model in Indonesian language learning on the material on the Concept of Changes in the Form of Objects in class III of Merarai 9 State Elementary School. The results of the learning implementation show that the application of the STEAM integrated PBL model can improve the 4C abilities of third grade elementary school students. Problem Based Learning (PBL) learning syntax was implemented with a percentage of 100%. The posttest results showed that 90% of students achieved scores above the KBM.